2021
DOI: 10.1038/s41467-021-21512-w
|View full text |Cite
|
Sign up to set email alerts
|

Control of oviductal fluid flow by the G-protein coupled receptor Adgrd1 is essential for murine embryo transit

Abstract: Dysfunction of embryo transport causes ectopic pregnancy which affects approximately 2% of conceptions in the US and Europe, and is the most common cause of pregnancy-related death in the first trimester. Embryo transit involves a valve-like tubal-locking phenomenon that temporarily arrests oocytes at the ampullary-isthmic junction (AIJ) where fertilisation occurs, but the mechanisms involved are unknown. Here we show that female mice lacking the orphan adhesion G-protein coupled receptor Adgrd1 are sterile be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 58 publications
0
38
0
Order By: Relevance
“…The fact that antibody binding to the PTX domain of the N-terminus of GPR133 increases signaling, while PTX deletion has the opposite effect, suggests a crucial function for this particular domain in receptor function, possibly through ligand binding. This hypothesis is supported by the recent identification of Plexin Domain-Containing Protein 2 (Plxdc2) as an activating ligand of GPR133, via an interaction with the PTX domain (Bianchi et al, 2021).…”
Section: Discussionmentioning
confidence: 86%
“…The fact that antibody binding to the PTX domain of the N-terminus of GPR133 increases signaling, while PTX deletion has the opposite effect, suggests a crucial function for this particular domain in receptor function, possibly through ligand binding. This hypothesis is supported by the recent identification of Plexin Domain-Containing Protein 2 (Plxdc2) as an activating ligand of GPR133, via an interaction with the PTX domain (Bianchi et al, 2021).…”
Section: Discussionmentioning
confidence: 86%
“…We then compared the PTK7-GPR133 interaction side-by-side with PLXDC2, the recently described GPR133 ligand expressed in the female reproductive system (Bianchi et al ., 2021). However, we observed that PLXDC2 was neither detected in our initial screen in the context of patient-derived GBM cells, nor did it show detectable co-purification with GPR133 in HEK293T cells in our hands (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the identity of extracellular interactors of GPR133 in GBM, as well as whether mechanical forces generated by their binding are involved in receptor signaling, remain unknown. The only previously known GPR133 ligand, the transmembrane cell surface protein PLXDC2 (Plexin Domain Containing 2), was recently shown to mediate an interaction with GPR133 critical to the female reproductive system in mice (Bianchi et al , 2021). However, the underlying mechanism of this interaction, including effects on NTF-CTF dissociation and mechano-activation requirements, were not assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Although not the primary focus of this review, it is important to consider the significant progress made in the study of proteins in oviduct fluid. In the context of this article, proteins are considered only as a potential source of amino acids, although it is recognised that the oviduct proteome will play many critical roles beyond amino acid supply, e.g., [ 13 , 27 ]. Protein concentrations in oviduct fluid are 5–10% those in serum [ 3 , 28 ] and the origin and transport of proteins across the oviduct and their dialogue with the gametes and embryo has become an active area of research: e.g., see reviews by [ 29 , 30 , 31 , 32 ].…”
Section: Proteins In Oviduct Fluid; Putative Functions and Regulationmentioning
confidence: 99%